Comparative Analysis of Temperature Coefficients and Thermal Performance Degradation of 50 WP Monocrystalline and Polycrystalline Solar Panels using Artificial Radiation Simulation - Asep mula Kurnia (PT FORMOSA CENDEKIA GLOBAL, 2026)
Solar panel performance is strongly influenced by thermal conditions during the energy conversion process, especially in high-temperature environments such as tropical regions. An increase in photovoltaic module surface temperature can reduce output voltage and directly affect power output and system efficiency. This study aims to compare the temperature coefficient and thermal degradation characteristics of 50 WP monocrystalline and polycrystalline solar panels through an experimental approach using artificial radiation simulation. The research method used two photovoltaic modules, namely monocrystalline and polycrystalline types, connected to a Maximum Power Point Tracking (MPPT) charge controller system. A 1000 W halogen lamp was used as an artificial radiation source to simulate solar exposure and increase the panel surface temperature. Electrical parameters, including voltage and current, were collected in real time using Modbus RS485 communication and monitored through computer software. Panel surface temperature was measured using an RS485-based temperature sensor integrated into the data acquisition system. The analysis included calculation of output power, power variation with temperature, and determination of the temperature coefficient based on experimental data. The results showed that both panel types experienced performance reduction as temperature increased, but with different degradation characteristics. In contrast, the polycrystalline panel showed more stable thermal behavior. These findings indicate that temperature has an important role in photovoltaic system performance and should be considered when selecting solar panels for high-temperature environments. This study also demonstrates that artificial radiation simulation can be used as an alternative method for thermal characterization, although it has limitations compared to standard solar radiation conditions.